The utilization of information technology among doctors in Kelantan a comparative cross-sectional study between medical officers in the tertiary centers (HKB & HUSM) and district hospitals and health clinics. - Fakri, Nik Mohd Rizal Mohd (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2005)
Objectives To compare the knowledge, skills and attitudes of IT between doctors in HUSM, those in health ministry hospitals and health clinics and those from general practice. Methods A comparative cross-sectional study among 84 medical officers from HUSM, 84 medical officers from health ministry hospitals and health clinics and 84 general practitioners in Kelantan. A structured self-administered questionnaire was used. There were three domains in the questionnaire; knowledge, attitudes and practices and skills (30 questions for each domain). There were three options for the administration of the questionnaire; paper-based, computer-based and web-based. The questionnaire was tested for reliability and validity among 30 medical officers in HUSM. Results There was no significant different in knowledge and attitude among all three groups of doctors. However in skills, there was significant different among the doctors from general practitioners as compared to other two groups. Conclusions All three groups of doctors from health ministry hospitals and health clinics and those from general practice had good knowledge and positive attitude of information technology. However doctors from general practice showed a significantly lower skills in information technology.